Method for producing conductive polymer solution and method for producing conductive laminate
Patent Information
- Application Number
- JP2024206559
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-26
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0007】 本発明の製造方法にあっては、水系分散媒から導電性複合体を分取し、これにアミン化合物又は第四級アンモニウム化合物を反応させる方法を採用しているので、従来方法のように水系分散媒に対して有機溶剤を大量に投入する必要がない。この結果、製造プロセスの安全性を高め、廃液処理の負担が減り、環境負荷を低減することができる。 また、本発明の製造方法によって得られた導電性高分子溶液を用いて製造した導電層は良好な導電性を示し、帯電防止性を発揮し得る。
Smart Images

Figure 2025027044000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a conductive polymer solution containing a π-conjugated conductive polymer, and a method for producing a conductive laminate. [Background technology]
[0002] Although π-conjugated conductive polymers, whose main chains are composed of π-conjugated systems, are basically poorly soluble in water, their conductivity is increased and they become water-dispersible by forming a complex with a polyanion having a hydrophilic anionic group. In addition, a method is known in which the anionic group of this conductive complex is made hydrophobic by reacting it with an amine compound or an epoxy compound, thereby dispersing it in an organic solvent (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-97680 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the conventional manufacturing method disclosed in Patent Document 1 and the like, a large amount of organic solvent is added to an aqueous dispersion medium containing a conductive composite in order to dissolve and react a hydrophobic amine compound or epoxy compound. This requires VOC management during the reaction and waste liquid treatment after the reaction. From the viewpoint of improving the safety of the manufacturing process and reducing the environmental load, a manufacturing method that does not require the addition of an organic solvent to an aqueous dispersion medium is required.
[0005] The present invention provides a method for producing a conductive polymer solution that can reduce the amount of organic solvent used, and a method for producing a conductive laminate using the obtained conductive polymer solution. [Means for solving the problem]
[0006] [1] A method for producing a conductive polymer solution, comprising the steps of: adding a catalyst and an oxidizing agent to a reaction solution containing a monomer capable of forming a π-conjugated conductive polymer, a polyanion, and water, thereby oxidatively polymerizing the monomer to form a conductive polymer powder containing the π-conjugated conductive polymer and the polyanion; separating the conductive polymer powder from the reaction solution; and mixing the separated conductive polymer powder with an amine compound or a quaternary ammonium compound, and a solvent to obtain a conductive polymer solution containing the conductive polymer powder reacted with the amine compound or the quaternary ammonium compound, wherein a content ratio of the monomer:the polyanion in the reaction solution is (1:0.5) to (1:1) on a mass basis. [2] A method for producing a conductive polymer powder containing a π-conjugated conductive polymer and the polyanion by adding a catalyst and an oxidizing agent to a reaction liquid containing a monomer capable of forming a π-conjugated conductive polymer, a polyanion, and water, thereby oxidatively polymerizing the monomer; separating the conductive polymer powder from the reaction liquid; washing the separated conductive polymer powder with water; and mixing the washed conductive polymer powder with an amine compound or a quaternary ammonium compound and a solvent to obtain a conductive polymer solution containing the conductive polymer powder reacted with the amine compound or the quaternary ammonium compound, The method for producing a conductive polymer solution, wherein the content ratio of the monomer:the polyanion in the reaction solution is (1:0.5) to (1:1) on a mass basis. [3] The method for producing a conductive polymer solution according to [1] or [2], wherein the solvent contains an alcohol-based solvent or a ketone-based solvent. [4] The method for producing a conductive polymer solution according to [1] or [2], wherein the solvent contains isopropanol or methyl ethyl ketone. [5] The method for producing a conductive polymer solution according to any one of [1] to [4], wherein the amine compound is trioctylamine or tributylamine. [6] The method for producing a conductive polymer solution according to any one of [1] to [5], wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) or the polyanion is polystyrenesulfonic acid. [7] The method for producing a conductive polymer solution according to any one of [1] to [6], further comprising adding a binder component to the conductive polymer solution. [8] The method for producing a conductive polymer solution according to [7], wherein the binder component is an ultraviolet-curable acrylic resin. [9] A method for producing a conductive laminate, comprising the steps of obtaining a conductive polymer solution by the production method according to any one of [1] to [8], and applying the conductive polymer solution to at least a partial surface of a substrate.
[10] The method for producing the conductive laminate according to [9], comprising drying the coating film obtained by the coating and then irradiating the coating film with ultraviolet light to cure the ultraviolet-curable acrylic resin contained in the coating film, thereby forming a conductive layer. Effect of the Invention
[0007] In the manufacturing method of the present invention, a conductive complex is separated from an aqueous dispersion medium and reacted with an amine compound or a quaternary ammonium compound, so there is no need to add a large amount of an organic solvent to the aqueous dispersion medium as in the conventional method, which increases the safety of the manufacturing process, reduces the burden of waste liquid treatment, and reduces the environmental load. Furthermore, a conductive layer produced using the conductive polymer solution obtained by the production method of the present invention exhibits good conductivity and can exhibit antistatic properties.
[0008] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range.
[0010] <Method for producing conductive polymer solution> A first aspect of the present invention is a method for producing a conductive polymer solution, comprising: a step (polymerization step) of oxidatively polymerizing the monomer by adding a catalyst and an oxidizing agent to a reaction solution containing a monomer capable of forming a π-conjugated conductive polymer, a polyanion, and water, thereby forming a conductive polymer powder containing the π-conjugated conductive polymer and the polyanion; a step (isolation step) of separating the conductive polymer powder from the reaction solution; and a step (modification step) of mixing the separated conductive polymer powder with an amine compound or a quaternary ammonium compound, and a solvent to obtain a conductive polymer solution containing the conductive polymer powder reacted with the amine compound or the quaternary ammonium compound, wherein the content ratio of the monomer:the polyanion in the reaction solution is (1:0.5) to (1:1) on a mass basis.
[0011] <Polymerization process> In this process, an aqueous solution (reaction solution) containing the monomer and the polyanion at a specific content ratio is prepared, and the monomer is polymerized to form a π-conjugated conductive polymer. In the reaction solution, the polyanion is naturally doped into the π-conjugated conductive polymer, and a conductive polymer powder containing a conductive complex consisting of the π-conjugated conductive polymer and the polyanion is formed. The content ratio (mass basis) of the π-conjugated conductive polymer:polyanion contained in the formed conductive complex is the same as the ratio of the content of the monomer contained in the aqueous solution immediately before the start of polymerization to the content of the polyanion. In other words, the content ratio of the monomer and the polyanion blended in the reaction solution is reflected in the content ratio of the π-conjugated conductive polymer and the polyanion in the formed conductive complex and conductive polymer powder.
[0012] The content ratio of the monomer to the polyanion in the reaction solution immediately before the start of polymerization is (1:0.5) to (1:1) on a mass basis, preferably (1:0.5) to (1:0.9), more preferably (1:0.5) to (1:0.8), and even more preferably (1:0.5) to (1:0.7). When the content is equal to or more than the lower limit of the above range, the doping effect of the polyanion is sufficiently exhibited, and a conductive polymer powder having better conductivity can be obtained. When the content is equal to or less than the upper limit of the above range, it is possible to obtain the doping effect of the polyanion, while forming a conductive polymer powder that has low dispersibility in water and can be easily precipitated.
[0013] The catalyst contained in the reaction liquid is not particularly limited as long as it polymerizes the monomers, and examples thereof include transition metal compounds such as ferric chloride, ferric sulfate, ferric nitrate, and cupric chloride. It is preferable to contain an oxidizing agent together with the catalyst. The oxidizing agent can return the reduced catalyst to its original oxidized state. Examples of the oxidizing agent include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate.
[0014] The content of the monomer contained in the reaction liquid immediately before the start of polymerization is, for example, preferably 0.1 mass % or more and 10 mass % or less, more preferably 0.2 mass % or more and 5 mass % or less, and even more preferably 0.3 mass % or more and 2 mass % or less, relative to the total mass of the reaction liquid. When the concentration is at least the lower limit of the above range, the conductive polymer powder formed can be easily separated. When the content is equal to or less than the upper limit of the above range, the polymerization reaction can be stably carried out, so that the formation of a complex with the polyanion present in the reaction system can be stably carried out, and a high-quality conductive polymer powder can be obtained.
[0015] The content of the polyanion in the reaction liquid immediately before the start of polymerization is preferably set based on the content ratio relative to the monomer.
[0016] The content of the oxidizing agent in the reaction liquid immediately before the start of polymerization is, for example, preferably 0.01 mass % or more and 3 mass % or less, more preferably 0.1 mass % or more and 2 mass % or less, and even more preferably 0.3 mass % or more and 1 mass % or less, relative to the total mass of the reaction liquid. When it is at least the lower limit of the above range, the conductive polymer powder can be easily formed. When the content is equal to or less than the upper limit of the above range, the polymerization reaction can be stably carried out, so that the formation of a complex with the polyanion present in the reaction system can be stably carried out, and a high-quality conductive polymer powder can be obtained.
[0017] From the viewpoint of accelerating the polymerization reaction, the reaction liquid may be heated and stirred to cause the reaction. The heating temperature of the reaction liquid may be, for example, 60 to 100°C. When the content is equal to or more than the lower limit of the above range, the polymerization reaction can be sufficiently promoted. When the content is equal to or less than the upper limit of the above range, deterioration of the π-conjugated conductive polymer due to heat can be suppressed. The reaction time at the heating temperature within the above range can be, for example, about 1 to 10 hours.
[0018] The solvent constituting the reaction solution may be any solvent capable of dissolving the monomer and the polyanion and in which the conductive polymer powder formed is difficult to dissolve, and is preferably an aqueous solvent containing water. In view of the purpose of the present invention, the content of water relative to the total solvent contained in the reaction solution is, for example, preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and may be 100% by mass. As the solvent other than water, a monohydric alcohol is preferable.
[0019] After the polymerization reaction, it is possible to wait for a while until the conductive polymer powder precipitates in the reaction liquid. For example, the conductive polymer powder can be made easy to separate by leaving the reaction liquid after the reaction at rest, slowly stirring the reaction liquid after the reaction, cooling the reaction liquid after the reaction to about -20° C. to 4° C., etc. In any of the methods, the conductive polymer powder can be naturally precipitated due to its property of being difficult to dissolve in water.
[0020] The obtained conductive polymer powder is an aggregate of particles of a conductive complex containing a π-conjugated conductive polymer and a polyanion.
[0021] [π-conjugated conductive polymers] The π-conjugated conductive polymer may be any conductive organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.
[0022] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable from the viewpoints of conductivity, transparency, and heat resistance. The conductive polymer powder may contain one type of π-conjugated conductive polymer, or two or more types of polymers.
[0023] (Polyanion) The polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for the π-conjugated conductive polymer, thereby improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer in which a single monomer is polymerized, or a copolymer in which two or more monomers are polymerized. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity. The polyanions may be used alone or in combination of two or more kinds. The mass average molecular weight of the polyanion is preferably from 20,000 to 1,000,000, more preferably from 100,000 to 500,000. The mass average molecular weight is the average molecular weight based on mass measured by gel permeation chromatography and calculated in terms of pullulan.
[0024] The polyanion is doped into the π-conjugated conductive polymer to form a conductive complex having electrical conductivity. The content ratio of the π-conjugated conductive polymer and the polyanion in the conductive complex is preferably as follows:
[0025] The content ratio of the π-conjugated conductive polymer to the polyanion in the conductive complex is, on a mass basis, from (1:0.5) to (1:1), preferably from (1:0.5) to (1:0.9), more preferably from (1:0.5) to (1:0.8), and even more preferably from (1:0.5) to (1:0.7). When the content is at least the lower limit of the above range, the doping effect of the polyanion is sufficiently exhibited, and the conductivity of the conductive polymer powder formed by the conductive complex is further improved. When the content is equal to or less than the upper limit of the above range, the conductive polymer powder has low dispersibility in water and can be easily precipitated in water while obtaining the doping effect of the polyanion.
[0026] <Preparative process> The separation step is a step of separating and recovering the conductive polymer powder containing the conductive complex formed in the reaction solution from the reaction solution. Examples of the separation method include a method of allowing the conductive polymer powder to naturally settle at the bottom of a container containing the reaction solution and then removing the supernatant, a method of filtering the reaction solution to obtain the conductive polymer powder on a filter, and a method of forming pellets of the conductive polymer powder at the bottom of a container containing the reaction solution by centrifugation. Among these, the method of isolating by filter filtration is preferred because it is simple and easy.
[0027] The conductive polymer powder immediately after being recovered from the reaction liquid may be washed with water or an organic solvent since it still has reaction liquid containing a catalyst, an oxidizing agent, etc. adhering thereto. Specifically, the conductive polymer powder can be washed, for example, by adding the conductive polymer powder to a washing liquid made of water or an organic solvent, stirring the mixture, and then filtering it again, or by pouring the washing liquid over the conductive polymer powder on the filter, etc. Water is preferred as the washing liquid.
[0028] <Modification process> In this step, the conductive polymer powder obtained in the separation step is reacted with an amine compound or a quaternary ammonium compound to hydrophobically modify some of the anion groups (excess anion groups not involved in the dope) of the polyanion constituting the conductive polymer powder, thereby making it possible to dissolve the conductive polymer powder in an organic solvent. At this time, the conductive polymer powder can be easily reacted by mixing the conductive polymer powder with an amine compound or a quaternary ammonium compound and a solvent.
[0029] It is believed that when an amine compound reacts with a portion of the anionic groups of the polyanion, the following substituent (B) is formed, and when a quaternary ammonium compound reacts with a portion of the anionic groups of the polyanion, the following substituent (C) is formed.
[0030] (Substituent B) The substituent (B) is presumed to be a group represented by the following formula (B).
[0031] -H.N. + R 11 R 12 R 13 (B) [In formula (B), R 11 ~R 13 are each independently a hydrogen atom or a hydrocarbon group which may have a substituent, provided that R 11 ~R 13 At least one of the groups is a hydrocarbon group which may have a substituent.]
[0032] In the substituent (B), the bond at the left end represents the bond between the negative charge of the anionic group and the positive charge of the amine compound. Examples of anionic groups that can be negatively charged include "-SO3 - " is an anionic group in which an active proton is bonded to an oxygen atom.
[0033] R in chemical formula (B) 11 ~R 13 is a hydrogen atom or a hydrocarbon group which may have a substituent. 11 ~R 13 is a substituent derived from an amine compound described later. Examples of the hydrocarbon group in the chemical formula (B) include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. Examples of the aliphatic hydrocarbon group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the substituent on the aliphatic hydrocarbon group include a phenyl group and a hydroxyl group. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. Examples of the substituent on the aromatic hydrocarbon group include an alkyl group having 1 to 5 carbon atoms and a hydroxyl group.
[0034] The amine compound is at least one selected from the group consisting of primary amines, secondary amines, and tertiary amines. The amine compound that reacts with the conductive composite may be one type or two or more types. Examples of primary amines include aniline, toluidine, benzylamine, and ethanolamine. Examples of secondary amines include diethanolamine, dimethylamine, diethylamine, dipropylamine, diphenylamine, dibenzylamine, and dinaphthylamine. Examples of tertiary amines include triethanolamine, trimethylamine, triethylamine, tripropylamine, tributylamine, trihexylamine, trioctylamine, triphenylamine, tribenzylamine, and trinaphthylamine. Among the amine compounds, tertiary amines are preferred because they can increase the electrical conductivity of the conductive composite of this embodiment, and at least one of trioctylamine and tributylamine is more preferred.
[0035] In order to increase the solubility in organic solvents, the amine compound preferably has a substituent on the nitrogen atom having 4 or more carbon atoms, more preferably has a substituent of 6 or more carbon atoms, and even more preferably has a substituent on the nitrogen atom having 8 or more carbon atoms. The upper limit of the carbon number of the substituent on the nitrogen atom is not particularly limited, and taking into consideration the solubility in solvents and reactivity, it is, for example, preferably 50 or less, more preferably 40 or less, and even more preferably 30 or less.
[0036] (Substituent C) The substituent (C) is presumed to be a group represented by the following formula (C).
[0037] -N + R 11 R 12 R 13 R 14 (C) [In formula (C), R 11 ~R 14 each independently represents a hydrocarbon group which may have a substituent.
[0038] In the substituent (C), the bond at the left end represents the bond between the negative charge of the anion group and the positive charge of the quaternary ammonium cation. Examples of an anion group that can be negatively charged include "-SO3 - " is an anionic group in which an active proton is bonded to an oxygen atom.
[0039] R in chemical formula (C) 11 ~R 14 represents a hydrocarbon group which may have a substituent. R in chemical formula (C) 11 ~R 14 is a substituent derived from a quaternary ammonium compound. Examples of the hydrocarbon group in chemical formula (C) include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. Examples of the aliphatic hydrocarbon group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the substituent on the aliphatic hydrocarbon group include a phenyl group and a hydroxyl group. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. Examples of the substituent on the aromatic hydrocarbon group include an alkyl group having 1 to 5 carbon atoms and a hydroxyl group.
[0040] Since the solubility in organic solvents is increased, the quaternary ammonium compound preferably has a substituent on the nitrogen atom having 4 or more carbon atoms, more preferably has a substituent on the nitrogen atom having 6 or more carbon atoms, and even more preferably has a substituent on the nitrogen atom having 8 or more carbon atoms. The upper limit of the carbon number of the substituent on the nitrogen atom is not particularly limited, and taking into consideration the solubility in solvents and reactivity, it is, for example, preferably 50 or less, more preferably 40 or less, and even more preferably 30 or less. In addition, the R 11 ~R 14 The total number of carbon atoms is preferably 8 to 44, more preferably 12 to 40, and further preferably 16 to 36. The number of carbon atoms in each of the substituents on the nitrogen atom may be the same or different.
[0041] Specific examples of quaternary ammonium compounds include quaternary ammonium salts such as tetra-n-octylammonium salt, tetramethylammonium salt, tetraethylammonium salt, tetrapropylammonium salt, tetrabutylammonium salt, tetraphenylammonium salt, tetrabenzylammonium salt, and tetranaphthylammonium salt. Examples of the counter anion of the ammonium cation include halogen ions such as bromide ion and chloride ion, and hydroxy ion.
[0042] The number of types of the amine compound and the quaternary ammonium compound reacted with the conductive polymer powder may be one or two or more.
[0043] The amount of the amine compound to be reacted with the conductive polymer powder is preferably 10 parts by mass or more and 1000 parts by mass or less, more preferably 50 parts by mass or more and 600 parts by mass or less, and even more preferably 80 parts by mass or more and 300 parts by mass or less, relative to 100 parts by mass of the conductive complex constituting the conductive polymer powder. When the amount is equal to or more than the lower limit of the above range, the hydrophobicity of the conductive complex is sufficiently improved and the solubility in organic solvents is increased. When the amount is equal to or less than the upper limit of the above range, a decrease in conductivity due to excessive modification of the conductive complex can be suppressed.
[0044] The amount of the quaternary ammonium compound to be reacted with the conductive polymer powder is preferably 10 parts by mass or more and 1000 parts by mass or less, more preferably 50 parts by mass or more and 600 parts by mass or less, and even more preferably 80 parts by mass or more and 300 parts by mass or less, relative to 100 parts by mass of the conductive complex constituting the conductive polymer powder. When the amount is equal to or more than the lower limit of the above range, the hydrophobicity of the conductive complex is sufficiently improved and the solubility in organic solvents is increased. When the amount is equal to or less than the upper limit of the above range, the decrease in conductivity due to excessive modification of the conductive complex can be suppressed.
[0045] An organic solvent is mixed into the conductive polymer powder before, simultaneously with, or after mixing with the amine compound or the quaternary ammonium compound.
[0046] The organic solvent is preferably one capable of dissolving the amine compound and the quaternary ammonium compound, and more preferably one capable of dissolving the hydrophobized conductive polymer powder. Such an organic solvent is preferably a water-soluble organic solvent. Here, the water-soluble organic solvent is an organic solvent that dissolves 1 g or more in 100 g of water at 20°C. The water-soluble organic solvent may be used alone or in combination of two or more.
[0047] Examples of the water-soluble organic solvent include alcohol-based solvents, ether-based solvents, ketone-based solvents, and nitrogen atom-containing solvents. Examples of alcohol-based solvents include methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 2-methyl-2-propanol, 1-butanol, 2-butanol, 2-methyl-1-propanol, allyl alcohol, ethylene glycol, propylene glycol, propylene glycol monomethyl ether, and ethylene glycol monomethyl ether. Examples of the ether solvent include diethyl ether, dimethyl ether, propylene glycol dialkyl ether, and diethylene glycol diethyl ether. Examples of the ketone solvent include diethyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl amyl ketone, diisopropyl ketone, methyl ethyl ketone, acetone, and diacetone alcohol.
[0048] Among the above, alcohol-based solvents and ketone-based solvents are preferred because they have excellent solubility for the conductive polymer powder and excellent coatability of the finally obtained conductive polymer solution. Among the alcohol-based solvents, isopropanol is particularly preferred. Among the ketone solvents, methyl ethyl ketone is particularly preferred.
[0049] The amount of the organic solvent mixed with the conductive polymer powder is, for example, preferably 95% by mass or more, more preferably 97% by mass or more, and even more preferably 99% by mass or more, based on the total mass of the conductive polymer powder, the amine compound or the quaternary ammonium compound, and the organic solvent. With this amount, the solubility of the conductive polymer powder in the conductive polymer solution obtained after mixing is improved.
[0050] The content of the hydrophobized conductive polymer powder (conductive complex) relative to the total mass of the conductive polymer solution obtained in this process is preferably 0.01 mass% or more and 5 mass% or less, more preferably 0.1 mass% or more and 3 mass% or less, and even more preferably 0.2 mass% or more and 1 mass% or less. When the content is at least the lower limit of the above range, the conductivity of the conductive layer formed by applying the conductive polymer powder is further increased. When the content is equal to or less than the upper limit of the above range, the solubility of the conductive polymer powder is improved.
[0051] The conductive polymer solution obtained in this step may be subjected to a dispersion treatment by stirring. The stirring method is not particularly limited, and may be a low shear stirring such as with a stirrer, or may be a high shear stirring using a dispersing machine (homogenizer, etc.).
[0052] (Dissolution vs. Dispersion) In this specification, for the conductive polymer powder, the conductive composite, the π-conjugated conductive polymer, and the polyanion, the dissolved state and the dispersed state in the solvent are not distinguished unless otherwise specified, because there is no means for distinguishing between a well-dispersed state and a uniformly dissolved state. In any case, if the conductive polymer is well dispersed, it does not easily settle and a uniform coating film can be formed. Therefore, the conductive polymer solution of the present invention may be called a conductive polymer dispersion liquid or a conductive polymer-containing liquid.
[0053] <Binder addition process> A binder component may be further added to the conductive polymer solution obtained in the modification step. The binder component is a resin or a precursor thereof other than the π-conjugated conductive polymer and the polyanion, and is a thermoplastic resin or a curable monomer or oligomer that is cured when the conductive layer is formed. The thermoplastic resin becomes the binder resin as it is, and the curable monomer or oligomer becomes the resin formed by curing. The conductive polymer solution may contain one type of binder component or two or more types of binder components.
[0054] Specific examples of binder resins derived from binder components include epoxy resins, acrylic resins (acrylic compounds), polyester resins, polyurethane resins, polyimide resins, polyether resins, melamine resins, and silicones.
[0055] The curable monomer or oligomer may be a thermosetting monomer or oligomer, or a photocurable monomer or oligomer. Here, the oligomer refers to a polymer having a mass average molecular weight of less than 10,000. Examples of the curable monomer include an acrylic monomer (acrylic compound), an epoxy monomer, an organosiloxane, etc. Examples of the curable oligomer include an acrylic oligomer (acrylic compound), an epoxy oligomer, a silicone oligomer (curable silicone), etc. When an acrylic monomer or an acrylic oligomer is used as the binder component, it can be easily cured by heating or irradiating with light.
[0056] When a curable monomer or oligomer is included, it is preferable to further include a curing catalyst. For example, when a thermosetting monomer or oligomer is included, it is preferable to include a thermal polymerization initiator that generates radicals by heating, and when a photocurable monomer or oligomer is included, it is preferable to include a photopolymerization initiator that generates radicals by light irradiation.
[0057] The content of the binder in the conductive polymer solution of this embodiment can be, for example, 10 parts by mass or more and 100,000 parts by mass or less with respect to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion. When the content is equal to or greater than the lower limit of the above range, the film formability and film strength can be improved when the conductive polymer solution of this embodiment is applied to a film substrate or the like. When the content is equal to or less than the upper limit of the above range, a decrease in electrical conductivity due to a decrease in the content ratio of the conductive polymer powder can be suppressed.
[0058] It is preferable to add one or more ultraviolet-curable acrylic resins as a binder component. The ultraviolet-curable acrylic resin is a monomer or oligomer (a polymer having a mass average molecular weight of less than 10,000) that is cured into an acrylic resin by irradiation with ultraviolet light during the formation of the conductive layer.
[0059] The ultraviolet-curable acrylic resin is preferably a polyfunctional (meth)acrylate monomer. Here, "(meth)acrylate" means "acrylate and / or methacrylate", "(meth)acrylic acid" means "acrylic acid and / or methacrylic acid", "(meth)acrylic resin" means "acrylic resin and / or methacrylic resin", "(meth)acryloyl group" means "acryloyl group and / or methacryloyl group", and "(meth)acryloyloxy group" means "acryloyloxy group and / or methacryloyloxy group".
[0060] The polyfunctional (meth)acrylate monomer is a monomer having two or more (meth)acryloyl groups, and examples thereof include difunctional (meth)acrylates, trifunctional (meth)acrylates, tetrafunctional to hexafunctional (meth)acrylates, and heptafunctional to decafunctional (meth)acrylates.
[0061] Examples of the bifunctional (meth)acrylate include esters of polyhydric alcohols and (meth)acrylic acid [e.g., di(meth)acrylate of glycol, di(meth)acrylate of glycerin, di(meth)acrylate of trimethylolpropane, di(meth)acrylate of 3-hydroxy-1,5-pentanediol, and di(meth)acrylate of 2-hydroxy-2-ethyl-1,3-propanediol]; esters of alkylene oxide adducts of polyhydric alcohols and (meth)acrylic acid [e.g., di(meth)acrylate of ethylene oxide adduct of trimethylolpropane, and di(meth)acrylate of ethylene oxide adduct of glycerin]; hydroxyl group-containing epoxy acrylates at both ends; esters of polyhydric alcohols, (meth)acrylic acid, and hydroxycarboxylic acids [e.g., hydroxypivalic acid neopentyl glycol di(meth)acrylate]. Here, it is not necessary to react all of the hydroxyl groups of the polyhydric alcohol with (meth)acrylic acid or an alkylene oxide adduct, and some hydroxyl groups may remain unreacted.
[0062] Examples of the trifunctional (meth)acrylate include tri(meth)acrylate of glycerin, tri(meth)acrylate of trimethylolpropane, tri(meth)acrylate of pentaerythritol, and tri(meth)acrylate of an ethylene oxide adduct of trimethylolpropane.
[0063] Examples of the tetra- to hexafunctional (meth)acrylate include tetra(meth)acrylate of pentaerythritol, penta(meth)acrylate of dipentaerythritol, hexa(meth)acrylate of dipentaerythritol, tetra(meth)acrylate of an ethylene oxide adduct of dipentaerythritol, penta(meth)acrylate of an ethylene oxide adduct of dipentaerythritol, and penta(meth)acrylate of a propylene oxide adduct of dipentaerythritol.
[0064] Examples of the hepta-10 functional (meth)acrylate compound include a reaction product of a diisocyanate compound, such as a compound obtained by reacting dipentaerythritol penta(meth)acrylate with hexamethylene diisocyanate, with a hydroxyl group-containing polyfunctional (meth)acrylate compound.
[0065] The content of the ultraviolet-curable acrylic resin in the conductive polymer solution of this embodiment is preferably from 10% by mass to 80% by mass, more preferably from 20% by mass to 70% by mass, and further preferably from 30% by mass to 60% by mass. When the content is at least as large as the lower limit of the above range, the film strength of the conductive layer to be formed can be further increased. When the content is equal to or less than the upper limit of the above range, the content of the conductive complex in the conductive layer to be formed can be increased, thereby making it possible to increase the conductivity of the conductive layer.
[0066] The content of the ultraviolet-curable acrylic resin in the conductive polymer solution of this embodiment can be, for example, 10 parts by mass or more and 10,000 parts by mass or less, preferably 100 parts by mass or more and 5,000 parts by mass or less, more preferably 300 parts by mass or more and 3,000 parts by mass or less, and even more preferably 500 parts by mass or more and 2,000 parts by mass or less, relative to 10 parts by mass of the total of the π-conjugated conductive polymer and the polyanion. When the content is equal to or greater than the lower limit of the above range, the film formability and film strength can be improved when the conductive polymer solution of this embodiment is applied to a film substrate or the like. When the content is equal to or less than the upper limit of the above range, a decrease in electrical conductivity due to a decrease in the content ratio of the conductive polymer powder can be suppressed.
[0067] (Other additives) The conductive polymer solution of this embodiment may contain additives other than the binder component, such as a surfactant, an inorganic conductive agent, a defoaming agent, an antioxidant, and an ultraviolet absorbing agent. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. A polymer surfactant such as polyvinylpyrrolidone may also be added. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers.
[0068] The amount of other additives added can be appropriately determined depending on the type of additive, but can be, for example, in the range of 0.001 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion.
[0069] <Conductive laminate> A second aspect of the present invention is a conductive laminate comprising a substrate and a conductive layer formed on at least a portion of the surface of the substrate, the conductive layer being made of a cured product of the conductive polymer solution obtained by the manufacturing method of the first aspect.
[0070] [Conductive layer] The conductive layer may be formed over the entire surface of any surface of the substrate, or over a portion of the entire surface. In the conductive film, it is preferable that a conductive layer of substantially uniform thickness is formed over substantially the entire surface of one surface or the other surface of the film substrate. When a conductive layer is formed only over a portion of the surface of the substrate, the conductive layer may be, for example, a fine conductive pattern such as a circuit or an electrode, or the conductive layer may be provided on the same surface and the conductive layer may be not provided on the same surface and may be roughly divided.
[0071] The average thickness of the conductive layer provided on at least a portion of the surface of the substrate is, for example, preferably 10 nm to 100 μm, more preferably 20 nm to 50 μm, and even more preferably 30 nm to 30 μm. When the average thickness of the conductive layer is equal to or greater than the lower limit, a sufficiently high conductivity can be exhibited, and when the average thickness is equal to or less than the upper limit, the adhesion of the conductive layer to the substrate is further improved.
[0072] The conductive layer included in the conductive laminate of this embodiment contains the conductive polymer powder. When the conductive polymer solution applied to the substrate contains a binder component, the conductive layer contains the binder component or a cured product of the binder component.
[0073] [Base material] The substrate constituting the conductive laminate of this embodiment may be a substrate made of an insulating material or a substrate made of a conductive material. The shape of the substrate is not particularly limited, and examples thereof include a shape mainly having a flat surface such as a film or a substrate. Examples of insulating materials include glass, synthetic resin, and ceramics. The conductive material may be a metal, a conductive metal oxide, carbon, or the like.
[0074] (Film substrate) When a film substrate is used as the substrate, the conductive laminate becomes a conductive film. The film substrate may be, for example, a plastic film made of a synthetic resin, such as ethylene-methyl methacrylate copolymer resin, ethylene-vinyl acetate copolymer resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyacrylate, polycarbonate, polyvinylidene fluoride, polyarylate, styrene-based elastomer, polyester-based elastomer, polyethersulfone, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyimide, cellulose triacetate, cellulose acetate propionate, etc. From the viewpoint of improving the adhesion between the film substrate and the conductive layer, the synthetic resin for the film substrate is preferably the same type of resin as the binder resin, and among these, a polyester resin such as polyethylene terephthalate is preferred.
[0075] The synthetic resin for the film substrate may be either amorphous or crystalline. The film substrate may be either unstretched or stretched. The film substrate may be subjected to a surface treatment such as a corona discharge treatment, a plasma treatment, or a flame treatment in order to further improve the adhesiveness of the conductive layer formed from the conductive polymer solution.
[0076] The average thickness of the film substrate is preferably 5 μm to 500 μm, more preferably 20 μm to 200 μm. If the average thickness of the film substrate is equal to or more than the lower limit, the film is less likely to break, and if the average thickness is equal to or less than the upper limit, the film can have sufficient flexibility. The average thickness of the film substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0077] (Glass substrate) Examples of the glass substrate include an alkali-free glass substrate, a soda-lime glass substrate, a borosilicate glass substrate, and a quartz glass substrate. If the substrate contains an alkali component, the conductivity of the conductive layer tends to decrease, so among the above glass substrates, an alkali-free glass is preferred. Here, the alkali-free glass refers to a glass composition in which the content of the alkali component is 0.1 mass% or less with respect to the total mass of the glass composition.
[0078] The average thickness of the glass substrate is preferably 50 μm or more and 3000 μm or less, and more preferably 100 μm or more and 1000 μm or less. If the average thickness of the glass substrate is equal to or more than the lower limit, the substrate is less likely to break, and if the average thickness is equal to or less than the upper limit, the substrate can contribute to making the conductive laminate thinner. The average thickness of the glass substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0079] <Method for manufacturing conductive laminate> A third aspect of the present invention is a method for producing a conductive laminate, the method including the steps of obtaining a conductive polymer solution by the method of the first aspect and applying the conductive polymer solution to at least a part of a surface of a substrate. The conductive laminate of the second aspect can be produced by the method of this aspect.
[0080] Examples of a method for applying (coating) the conductive polymer solution on any surface of a substrate include a method using a coater such as a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater, or a screen coater; a method using a sprayer such as an air spray, an airless spray, or a rotor dampening; and an immersion method such as dipping.
[0081] The amount of conductive polymer solution applied to the substrate is not particularly limited, but it is recommended to apply the solution uniformly and without unevenness, taking into consideration the conductivity and film strength, and to apply the solution at a rate of 0.01 g / m2 or less in terms of solid content. 2More than 10.0g / m 2 The following ranges are preferred:
[0082] The coating film made of the conductive polymer solution applied onto the substrate is dried to remove the solvent (dispersion medium), thereby obtaining a conductive laminate in which a conductive layer (conductive film) is formed by hardening the coating film. Methods for drying the coating film include heat drying, vacuum drying, etc. Examples of heat drying that can be used include hot air heating and infrared heating. When applying heat drying, the heating temperature is appropriately set depending on the dispersion medium used, but is usually within the range of 50° C. to 200° C. Here, the heating temperature is the set temperature of the drying device. A suitable drying time within the above heating temperature range is preferably 0.5 minutes to 30 minutes, more preferably 1 minute to 15 minutes.
[0083] When the conductive polymer solution contains an active energy ray-curable binder component, the method may further include an active energy ray irradiation step of irradiating the dried coating film with active energy rays. The active energy ray irradiation step can increase the rate of formation of the conductive layer, thereby improving the productivity of the conductive laminate. In the case where the active energy ray irradiation step is included, examples of the active energy ray used include ultraviolet rays, electron beams, visible light, etc. Examples of the light source of the ultraviolet ray that can be used include light sources such as ultra-high pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arcs, xenon arcs, and metal halide lamps. The illuminance of ultraviolet light is 100mW / cm 2 Illuminance of 100mW / cm or more is preferable. 2 If the radiation amount is less than 50 mJ / cm2, the active energy ray-curable binder component may not be cured sufficiently. 2 More than 50mJ / cm is preferable. 2If the irradiance is less than 100 nm, crosslinking may not be sufficient. In this specification, the illuminance and the integrated light amount are values measured using a Topcon UVR-T1 (industrial UV checker, photoreceiver: UD-T36, measurement wavelength range: 300 nm to 390 nm, peak sensitivity wavelength: about 355 nm). EXAMPLES
[0084] (Production Example 1) Production of polystyrene sulfonic acid 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate-containing solution, and 1000ml of the solvent from the obtained polystyrene sulfonic acid-containing solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This water washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid.
[0085] Example 1 A solution of 0.5 g of 3,4-ethylenedioxythiophene and 0.5 g of polystyrene sulfonic acid dissolved in 14.5 g of ion-exchanged water was mixed at 20° C. Next, 89.5 g of ion-exchanged water was added. The resulting mixed solution was kept at 20°C and, while stirring, a solution of 0.03 g of ferric sulfate dissolved in 4.97 g of ion-exchanged water and a solution of 1.1 g of ammonium persulfate dissolved in 8.9 g of ion-exchanged water were slowly added, and the resulting reaction solution was stirred for 24 hours to react. The above reaction yielded a powder-containing liquid containing a powder of a conductive complex (PEDOT-PSS, PEDOT:PSS mass ratio = approximately 1:1 in the range of (1:1) to (1:0.5)) containing poly(3,4-ethylenedioxythiophene), a π-conjugated conductive polymer, and polystyrenesulfonic acid, and water as a solvent. The resulting PEDOT-PSS powder was separated by filtration and washed twice with 100 g of water, yielding 1.0 g of PEDOT-PSS powder. 0.5 g of the obtained PEDOT-PSS powder was added with 0.5 g of trioctylamine and 249 g of isopropanol, and dispersed using a high-pressure homogenizer. The obtained conductive polymer solution was applied onto a PET film (Toray Industries, Inc., Lumirror T60) using a #4 bar coater, and dried at 100°C for 1 minute to obtain a first conductive film. Next, 40 g of pentaerythritol triacrylate, 1.6 g of Irgacure 184 (a photopolymerization initiator manufactured by BASF), and 8.4 g of propylene glycol monomethyl ether were added to 50 g of the conductive polymer solution to prepare a coating material. The resulting coating material was applied onto a PET film using a #12 bar coater, dried at 100° C. for 1 minute, and irradiated with 400 mJ of ultraviolet light to obtain a second conductive film.
[0086] Example 2 A first and a second conductive film were obtained in the same manner as in Example 1, except that 0.5 g of trioctylamine was changed to 0.5 g of tributylamine.
[0087] Example 3 A first and a second conductive film were obtained in the same manner as in Example 1, except that 249 g of isopropanol was changed to 249 g of methyl ethyl ketone.
[0088] Example 4 A solution of 0.5 g of 3,4-ethylenedioxythiophene and 0.25 g of polystyrene sulfonic acid dissolved in 14.75 g of ion-exchanged water was mixed at 20° C. Next, 89.5 g of ion-exchanged water was added. The resulting mixed solution was kept at 20°C and, while stirring, a solution of 0.03 g of ferric sulfate dissolved in 4.97 g of ion-exchanged water and a solution of 1.1 g of ammonium persulfate dissolved in 8.9 g of ion-exchanged water were slowly added, and the resulting reaction solution was stirred for 24 hours to react. The above reaction yielded a powder-containing liquid containing a powder of a conductive complex (PEDOT-PSS, PEDOT:PSS mass ratio = approximately 1:0.5 in the range of (1:1) to (1:0.5)) containing poly(3,4-ethylenedioxythiophene), a π-conjugated conductive polymer, and polystyrenesulfonic acid, and water as a solvent. The resulting PEDOT-PSS powder was separated by filtration and washed twice with 100 g of water, yielding 0.75 g of PEDOT-PSS powder. 0.5 g of the obtained PEDOT-PSS powder was added with 0.5 g of trioctylamine and 249 g of isopropanol, and dispersed using a high-pressure homogenizer. The obtained conductive polymer solution was applied onto a PET film (Toray Industries, Inc., Lumirror T60) using a #4 bar coater, and dried at 100°C for 1 minute to obtain a first conductive film. Next, in the same manner as in Example 1, a coating material was prepared and applied to obtain a second conductive film.
[0089] Example 5 A first and a second conductive film were obtained in the same manner as in Example 4, except that 0.5 g of trioctylamine was changed to 0.5 g of tributylamine.
[0090] Example 6 A first and a second conductive film were obtained in the same manner as in Example 4, except that 249 g of isopropanol was changed to 249 g of methyl ethyl ketone.
[0091] Comparative Example 1 To 0.5 g of 3,4-ethylenedioxythiophene, 104.5 g of ion-exchanged water was added. The resulting mixed solution was kept at 20°C and, while stirring, a solution of 0.03 g of ferric sulfate dissolved in 4.97 g of ion-exchanged water and a solution of 1.1 g of ammonium persulfate dissolved in 8.9 g of ion-exchanged water were slowly added, and the resulting reaction solution was stirred for 24 hours to react. The above reaction produced a powder-containing liquid containing a powder of poly(3,4-ethylenedioxythiophene), a π-conjugated conductive polymer (PEDOT:PSS mass ratio = 1:0), and water as a solvent. The resulting PEDOT powder was separated by filtration and washed twice with 100 g of water to obtain 0.5 g of PEDOT powder. 0.5 g of the obtained PEDOT powder was mixed with 0.5 g of trioctylamine and 249 g of isopropanol, and dispersed using a high-pressure homogenizer, but the process was discontinued because the powder did not disperse.
[0092] Comparative Example 2 A solution of 0.5 g of 3,4-ethylenedioxythiophene and 1.0 g of polystyrene sulfonic acid dissolved in 14.0 g of ion-exchanged water was mixed at 20° C. Next, 89.5 g of ion-exchanged water was added. The resulting mixed solution was kept at 20°C and, while stirring, a solution of 0.03 g of ferric sulfate dissolved in 4.97 g of ion-exchanged water and a solution of 1.1 g of ammonium persulfate dissolved in 8.9 g of ion-exchanged water were slowly added, and the resulting reaction solution was stirred for 24 hours to react. The above reaction yielded a conductive polymer aqueous dispersion containing a conductive complex (PEDOT-PSS, PEDOT:PSS mass ratio = approximately (1:2)) containing the π-conjugated conductive polymer poly(3,4-ethylenedioxythiophene) and polystyrenesulfonic acid, and water as a solvent. The conductive complex did not form powder in the resulting dispersion, and when filtered, all of the PEDOT-PSS passed through the filter paper, making it impossible to separate, so the process was discontinued.
[0093] <Evaluation method> [Surface resistance value] The surface resistance of the first and second conductive films of each example was measured using a resistivity meter (Hiresta manufactured by Nitto Seiko Analytech Co., Ltd.) with an applied voltage of 10 V. The measurement results are shown in Table 1. Note that "2.0E+07" in the table represents "2.0×10 7 " and similarly so for others.
[0094] [Table 1]
[0095] <Result> In the conductive polymer solution of each Example, the conductive polymer powder (conductive complex) reacted with the amine compound was uniformly dispersed in the organic solvent, and the conductive layer formed by applying this had good conductivity. On the other hand, the powder of Comparative Example 1, which did not contain polyanion, did not disperse at all in the organic solvent, and the conductive composite of Comparative Example 2, which contained a large amount of polyanion, did not form a powder that could be separated.
Claims
1. a step of adding a catalyst and an oxidizing agent to a reaction liquid containing a monomer capable of forming a π-conjugated conductive polymer, a polyanion, and water, thereby oxidatively polymerizing the monomer to form a conductive polymer powder containing the π-conjugated conductive polymer and the polyanion; A step of separating the conductive polymer powder from the reaction solution; and mixing the separated conductive polymer powder with trioctylamine and isopropanol to obtain a conductive polymer solution containing the conductive polymer powder reacted with trioctylamine, a content ratio of the monomer to the polyanion in the reaction solution is, on a mass basis, from (1:0.5) to (1:1).
2. a step of adding a catalyst and an oxidizing agent to a reaction liquid containing a monomer capable of forming a π-conjugated conductive polymer, a polyanion, and water, thereby oxidatively polymerizing the monomer to form a conductive polymer powder containing the π-conjugated conductive polymer and the polyanion; A step of separating the conductive polymer powder from the reaction solution; A step of washing the separated conductive polymer powder with water; and mixing the washed conductive polymer powder, trioctylamine, and isopropanol to obtain a conductive polymer solution containing the conductive polymer powder reacted with trioctylamine, a content ratio of the monomer to the polyanion in the reaction solution is, on a mass basis, from (1:0.5) to (1:1).
3. 3. The method for producing a conductive polymer solution according to claim 1, wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid.
4. 4. The method for producing a conductive polymer solution according to claim 1, further comprising adding a binder component to the conductive polymer solution.
5. The method for producing a conductive polymer solution according to claim 4 , wherein the binder component is an ultraviolet-curable acrylic resin.
6. A step of obtaining a conductive polymer solution by the manufacturing method according to any one of claims 1 to 5; and applying the conductive polymer solution to at least a partial surface of a substrate.
7. 7. The method for producing a conductive laminate according to claim 6, further comprising the steps of: drying the coating film obtained by the coating; and irradiating the coating film with ultraviolet light to cure the ultraviolet-curable acrylic resin contained in the coating film, thereby forming a conductive layer.
Citation Information
Patent Citations
Electroconductive polymer-containing liquid, manufacturing method thereof and manufacturing method of conductive film
JP2020097680A